Economic impacts of the COVID-19 pandemic on families of children with autism and other developmental disabilities - Pokoski, Olivia M.; Crain, Hayley; DiGuiseppi, Carolyn; Furnier, Sarah M.; Moody, Eric J.; Nadler, Cy; Pazol, Karen; Sanders, Jessica; Wiggins, Lisa D.; Durkin, Maureen S. (Frontiers in Psychiatry, 2024)
Background: To control the COVID-19 pandemic, many jurisdictions enacted public health measures that had vast socio-economic implications. In emergency situations, families of children with autism and other developmental disabilities (DDs) may experience increased economic hardship. Objectives: To assess impacts of the pandemic on parental employment and economic difficulties in families of children with autism and those with other DDs compared to the general population. Methods: The Study to Explore Early Development (SEED) is a multi-site case-control study of young children with autism, with another DD and in the general population (POP). In 2021, a COVID-19 Impact Assessment Questionnaire was sent to eligible participants (n=1,789) who had enrolled in SEED from 2017-early 2020. Parents completed a questionnaire on impacts of the pandemic in 2020 and completed the Child Behavior Checklist (CBCL) to measure behavioral and emotional health of their child during this time. Multiple logistic regression models were built for employment reduction, increased remote work, difficulty paying bills, and fear of losing one’s home. Unadjusted and adjusted odds ratios (aOR) and 95% confidence intervals (CI) were calculated. Results: The study included 274 children with autism, 368 with another DD, and 385 in the POP group. The mean age of 6.1 years did not differ between study groups. Parents of children with autism were less likely to transition to remote work (aOR [95% CI] = 0.6 [0.4, 1.0]) and more likely to report difficulty paying bills during the pandemic (1.8 [1.2, 2.9]) relative to parents of POP children. Lower income was associated with greater employment reduction, difficulty paying bills, and fear of losing their home, but inversely associated with transitioning to remote work. Parents from racial and ethnic minority groups were more likely than others to experience employment reductions, difficulty paying bills and fear losing their home. Caregivers of children with CBCL scores in the clinical range were more likely than others to fear losing their home (2. 1 [1.3, 3.4]). Conclusions: These findings suggest families of children with autism, low income families, and families of racial and ethnic minority groups experienced fewer work flexibilities and greater financial distress during the pandemic.